Detection of Carbapenemase Genes by Molecular Method among Gram-Negative Bacilli Isolates from Tertiary Care Hospital in Dhaka, Bangladesh - Mostofa, Hasbi Ara; Shamsuzzaman, SM; Hasan, Md Maniul; Sultana, Sharmeen; Afroz, Samira; Shormin, Moonmoon; Sultana, Sabia Shahin (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Imipenem resistance in Gram-negative bacilli is a global epidemic that is increasing day by day.To warn this global epidemic, identification and ongoing surveillance of carbapenem-resistant genes among Gram-negative bacilli needed. Objectives: This cross-sectional study was performed todetect the imipenem resistant genes among Gram-negative bacilli isolated from different samples in Dhaka medical college hospital. Methods: About 300 samples (wound swab, urine, endotracheal aspirate, blood, and sputum) were collected from July 2015 to June 2016. Among them, 204 isolates were Gram negative bacilli. Eighty imipenem resistant Gram-negative bacilli were isolated by disc diffusion method. Among them, carbapenem resistant genes (blaNDM-1, blaKPC, VIM, IMP) were detected by PCR. Results: A total 300 samples were analyzed. Out of 204 Gram negative bacilli,80 (39.21%) imipenem resistance was detected by the Disc Diffusion method. Out of 80 imipenem resistant organisms, 42 (52.5%) were positive for blaNDM-1, 6 (7.34%) were positive for blaKPC, 29 (36.25%) were positive for VIM, 13 (16.25%) were positive for IMP. Conclusion: This study illustrates the emergence of carbapenemase genes producing Gram negative bacilli isolates from patients. Close surveillance across all hospitals in Bangladesh is required. J Shaheed Suhrawardy Med Coll 2022; 14(1): 3-7